Pengembangan Media Pembelajaran Berbasis Web Google Sites Materi Klasifikasi Makhluk Hidup Untuk Meningkatkan Hasil Belajar Siswa Kelas VII SMP - Norhikmah Norhikmah; Ratna Yulinda; Rizky Febriyani Putri (CV.ITTC INDONESIA, 2026)
This research examines the creation of a web-based learning medium using Google Sites to teach the classification of living organisms, with the goal of enhancing the academic performance of seventh-grade junior high school students. The study aims to evaluate the effectiveness, practicality, and validity of the learning media that has been developed. The ADDIE development model consisting of Analysis, Development, Design, Implementation, and Evaluation served as the framework for this research. The media trial involved 22 students from class VII A at SMPN 1 Alalak. Data were collected through media student response questionnaires, validation forms, and assessments of learning outcomes administered as post-tests and pre-tests. The findings indicate that the developed media received a validity score of 90.6%, a practicality score of 91.4%, and an N-Gain of 0.80, categorized as high. These results further contribute to the advancement of digital learning resources, particularly web-based tools that can function as effective alternative instructional media. Google Sites is shown to support science learning through visual elements, videos, and interactive components such as quizzes, encouraging student engagement and potentially improving achievement. Based on these outcomes, The learning media developed using Google Sites for the material on classifying living organisms has been confirmed to be effective, practical, and valid in enhancing students’ learning outcomes in junior high school science classes.